Investigating the role of serine-ADP-ribosylation in human cells - Prokhorova, E (2022)
ADP-ribosylation (ADPr) is a widespread post-translational modification that controls many cellular processes, in particular DNA repair. Poly(ADP-ribose) polymerase 1 (PARP1) is the main ADPr enzyme that performs about 85-90% of DNA damage-induced ADPr. In response to DNA damage, PARP1 rapidly binds to DNA ends at the sites of DNA damage and modifies itself, histones and other proteins, thus promoting and regulating DNA repair. However, despite the critical role of PARP1 in DNA repair, for over 50 years the amino acid specificity of PARP1 remained controversial. Recently, our group and others discovered that PARP1 in complex with HPF1 predominantly performs ADPr at serine residues, both in response to exogenous DNA damage and under physiological conditions, and ARH3 is the hydrolase responsible for its timely reversal.